Pengembangan Instrumen Literasi Kimia pada Tema Silver Tarnish dan Polishing Silver - Fitri Yuliani; Eka Yusmaita; Fauzana Gazali (Edukimia, 2021)
This study aims to develop chemical literacy instrument that can be used to measure chemical literacy skills of students. The chemical literacy instrument in this study was arranged based on four domains of chemical literacy consisting of content, context, HOLS and affective aspects. This study uses the Model of Educational Reconstruction (MER) design. Content validity testing was conducted with five experts and analysed using CVR, while empirical testing of students was analysed using the Rasch model with Ministep application. Based on results of this research, chemical literacy instrument on silver tarnish and silver polishing topic is categorized as valid and reliability value is of 0,92.